Neurocognition and social cognition in remitted first-episode schizophrenia: correlation with VEGF serum levels - Yaqin Zhao (BMC Psychiatry, 2019)
Abstract Background Accumulating evidence suggests that serum vascular endothelial growth factor (VEGF) in many neurobiological processes potentially contributes to the pathophysiology of psychiatric disorders, particularly cognitive decline. The purpose of this study was to explore the differences in neurocognition, social cognition and VEGF among remitted first-episode schizophrenic patients, non-remitters and normal control subjects. Moreover, we investigated the association between serum VEGF levels and cognitive functions. Method 65 remission (RS) and 45 nonremission patients (NRS) after first-episode schizophrenia, as well as 58 healthy controls (HC) were enrolled in this study. Social cognition was assessed using the Chinese Facial Emotion Test (CFET); neurocognition was measured with a test battery consisting of Hopkins Verbal Learning Test-Revised, Verbal Fluency Test, Trail Making Tests, Digit Span Tests (DST) and Stroop Tests. Blood samples were collected for VEGF measurements. Data was analyzed with SPSS 22.0 (Chicago, IL, USA). Results On nearly all neurocognitive tests (except for DST), RS performed significantly worse than HC but better than NRS (P < 0.05). NRS, but not RS, exhibited markedly poorer social cognition than HC (except for Happiness and Surprise subscales of the CFET) (P < 0.05). VEGF levels showed a gradient change among three groups (HC > RS > NRS). Conclusion Compared to HC, RS demonstrated poorer neurocognitive but intact social cognition functioning. These results indicate that VEGF levels decreased gradually with the severity of cognitive impairment in schizophrenia. VEGF may be involved in the pathological mechanism of cognitive performance in RS.